2021
DOI: 10.3390/ijerph18105207
|View full text |Cite
|
Sign up to set email alerts
|

Of Pandemics and Zombies: The Influence of Prior Concepts on COVID-19 Pandemic-Related Behaviors

Abstract: We use a concepts and categories research perspective to explore how prior conceptual knowledge influences thinking about a novel disease, namely COVID-19. We collected measures of how similar people thought COVID-19 was to several existing concepts that may have served as other possible comparison points for the pandemic. We also collected participants’ self-reported engagement in pandemic-related behaviors. We found that thinking the COVID-19 pandemic was similar to other serious disease outbreaks predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Although this would eliminate some nuance from participants’ responses, this may make it easier for participants to respond and decrease the levels of attrition observed in this study. Further research must also be conducted to see how illness behavior interacts with specific pandemic-related behavior [ 25 ], especially as the pandemic continues to weigh on the world.…”
Section: Discussionmentioning
confidence: 99%
“…Although this would eliminate some nuance from participants’ responses, this may make it easier for participants to respond and decrease the levels of attrition observed in this study. Further research must also be conducted to see how illness behavior interacts with specific pandemic-related behavior [ 25 ], especially as the pandemic continues to weigh on the world.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rhetoric that described COVID-19 as similar to the flu may have instilled a belief that it is a less serious disease, which in turn may have suggested to people that there exist reasonable treatments for the symptoms. In recent work(Marsh et al, 2021a) we have found that comparing COVID-19 to the flu does reduce willingness to engage in our measured mitigation individual actions. More generally, understanding the relationship between ability to treat symptoms and seriousness in this direction would suggest that when public health officials downplay the seriousness of an emerging disease, they suggest to people experts' ability to treat its symptoms.…”
mentioning
confidence: 82%
“…The reported measures were part of a larger longitudinal study investigating people’s perceptions of their communities’ response to COVID-19 (for analyses using other variables or discussing other parts of the project see Marsh et al, 2021a; Packer et al, 2021). We collected data at four time points: Time 1 (early April): April 6, 2020; Time 2 (late April): April 21, 2020–April 23, 2020; Time 3 (June): June 5, 2020–June 8, 2020; and Time 4 (October): October 1, 2020–October 4, 2020 1…”
Section: Methodsmentioning
confidence: 99%
“…Measures were part of a larger study on US residents' experiences during COVID‐19; for analyses of other variables see Marsh et al. (2021a, 2021b). We collected data at five time points: T1: 4/6/2020; T2: 4/21/20; T3: 6/5/20; T4: 10/1/20; and T5: 3/25/21.…”
Section: Methodsmentioning
confidence: 99%
“…We compared effects for community identities to effects for the identity that participants self-nominated as most important to them at the start of the pandemic. Measures were part of a larger study on US residents' experiences during COVID-19; for analyses of other variables see Marsh et al (2021aMarsh et al ( , 2021b. We collected data at five time points: T1: 4/6/2020; T2: 4/21/20; T3: 6/5/20; T4: 10/1/20; and T5: 3/25/21.…”
Section: Introductionmentioning
confidence: 99%